2018
DOI: 10.1186/s12985-018-0992-9
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distribution and relative risk of Anjozorobe virus (Thailand orthohantavirus) infection in black rats (Rattus rattus) in Madagascar

Abstract: BackgroundHantavirus infection is a zoonotic disease that is associated with hemorrhagic fever with renal syndrome and cardiopulmonary syndrome in human. Anjozorobe virus, a representative virus of Thailand orthohantavirus (THAIV), was recently discovered from rodents in Anjozorobe-Angavo forest in Madagascar. To assess the circulation of hantavirus at the national level, we carried out a survey of small terrestrial mammals from representative regions of the island and identified environmental factors associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 54 publications
4
13
3
Order By: Relevance
“…The overall conservative prevalence estimate of 2.7% from the national-scale study, obtained using 2 ELISA assays, is similar to results from studies in some Africa countries where other confirmatory tests were used (3.9% in Cote d'Ivoire and 2.4% in the Democratic Republic of the Congo) (4,13). Although we believe some seropositive persons may have been exposed to other Murinae-associated hantaviruses, considering both ELISA results in humans and rodent infection data together (7), our observations are consistent with evidence that most were exposed to ANJZV. Specifically, the ANJZV ELISA detected more seropositive persons than the commercial kit, and the cosmopolitan Seoul virus, if present in rodents in Madagascar, is at low prevalence or patchily distributed (7).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The overall conservative prevalence estimate of 2.7% from the national-scale study, obtained using 2 ELISA assays, is similar to results from studies in some Africa countries where other confirmatory tests were used (3.9% in Cote d'Ivoire and 2.4% in the Democratic Republic of the Congo) (4,13). Although we believe some seropositive persons may have been exposed to other Murinae-associated hantaviruses, considering both ELISA results in humans and rodent infection data together (7), our observations are consistent with evidence that most were exposed to ANJZV. Specifically, the ANJZV ELISA detected more seropositive persons than the commercial kit, and the cosmopolitan Seoul virus, if present in rodents in Madagascar, is at low prevalence or patchily distributed (7).…”
Section: Discussionsupporting
confidence: 85%
“…Seropositive participants came from 20 of the 28 study sites (0-13.3% per site) distributed all over Madagascar (Table 1; Figure). Univariate generalized linear mixed models with site-zone as random effect indicated no effect of age, sex, or location (urban or rural), but we did find a slight suggestion of increased exposure in sites where our previous study (7) had detected infected rats (OR 3.0, 95% CI 0.78-11.5; p = 0.11).…”
contrasting
confidence: 69%
See 1 more Smart Citation
“…For example, in an urban area in Salvador, Brazil, Seoul virus antibodies were found in R. norvegicus serum samples 81 . A molecular survey conducted in Madagascar detected the Anjozorobe virus (Thailand Orthohantavirus) strain in R. rattus and M. musculus, suggesting viral spillover 82 .…”
Section: Hantavirus (Hv)mentioning
confidence: 99%
“…A total of 1242 samples were collected from 7 representative species of rodents found in Madagascar. A total of 111/897 samples (12.4%) of Rattus rattus species and 2 out of 125 (1.6%) samples of Mus musculus species of rodents were found to be positive with nested PCR for the infection of Anjozorobe virus [55]. The study suggested a high zoonotic transmission risk to the human population living in households given the prevalence of Anjozorobe virus in household-dwelling rodent species [55].…”
Section: Madagascarmentioning
confidence: 90%